Isolation and Characterization of Polyaromatic Hydrocarbons Degrading Bacteria from Compost Leachate - El- Din, Said M. Badr; Moussa, Tarek A; Moawad, Hassan; A Sharaf, Omaima (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Polycyclic aromatic hydrocarbon (PAHs) degrading bacteria were isolated from compost leachate (CL) that collected from a composting site located in central Scotland, UK. Isolation was carried out by enrichment using phenanthrene (PHR), Pyrene (PYR) and Benzo(a)pyrene (BaP) as the sole source of carbon and energy. The isolates were characterized using a variety of phenotypic, morphologic and molecular properties. Six different isolates were collected based on the difference in morphological and biochemical tests by using API 20E and API NE, also for their efficiency in PAHs utilization. The 16S rDNA sequence analysis confirmed the results of biochemical identification, as both of biochemical and molecular identification of the isolates assigned them to Bacillus licheniformis, Pseudomonas aeruginosa, Alcaligenes faecalis, Serratia marcescens, Enterobacter cloacae and Providenicia rettgeri which were identiï¬ed as the prominent PAHs-utilizers isolated from (CL). This study indicates that the (CL) samples contain a diverse population of PAHs-degrading bacteria and the use of (CL) may have a potential for bioremediation of PAHs contaminated sites.